Electrolytic corrosion liquid and display method of maraging steel original austenite grain boundary

By using electrolytic corrosion liquid of a specific formula, electrolytic corrosion of martensite aging steel, the problem of difficulty in displaying the original austenite grain boundaries in the prior art is solved, and the clear display of the grain boundaries and accurate measurement of grain size are achieved, which improves the efficiency of obtaining experimental data.

CN119666512APending Publication Date: 2025-03-21ADVANCED TECH BAZHOU SPECIAL POWDER CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411696096.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively display the original austenite grain boundaries of martensite aging steel, resulting in limited research on material performance optimization and phase change mechanism.

Method used

A specific electrolytic corrosion solution formula is used, including anhydrous ethanol, concentrated nitric acid, hydrochloric acid, deionized water, copper sulfate and copper chloride, and the original austenite grain boundaries of martensite aging steel are clearly displayed through electrolytic corrosion methods.

Benefits of technology

The accurate and clear display of the original austenite grain boundaries is achieved, which can accurately determine the grain size of the austenite and improve the acquisition efficiency and accuracy of experimental data.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666512A_ABST
    Figure CN119666512A_ABST
Patent Text Reader

Abstract

The invention provides an electrolytic corrosion liquid and a display method of maraging steel original austenite grain boundaries, and relates to the technical field of physicochemical metallographic detection.The method comprises the steps that firstly, component design is conducted on the basis of a CALPHAD method, maraging steel is prepared through an injection molding method, and the original austenite grain boundaries are represented through electrolytic corrosion; the electrolytic corrosion liquid comprises the following components: 5-6 ml of absolute ethyl alcohol, 2-3 ml of concentrated nitric acid, 1.5-2.5 ml of hydrochloric acid, 2-2.5 ml of deionized water, 1-2 g of copper sulfate and 1-2 g of copper chloride, the electrolysis voltage is 8-10 V, the electrolysis current is 2-5 A / cm < 2 >, electrolysis is performed 2-4 times, and the electrolysis time is 8-12 s each time. According to the method, the grain boundary of the original austenite can be accurately and clearly observed by preparing the components of the corrosive liquid, so that the grain size of the austenite is further determined, and the method has important significance in counting the grain size of the austenite and efficiently and accurately obtaining experimental data.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of physical and chemical metallographic detection, in particular to a method for displaying original austenite grain boundaries of electrolytic corrosion liquid and maraging steel. Background Art

[0002] Maraging steel has excellent mechanical properties, especially in terms of strength and wear resistance, due to its unique martensitic phase transformation mechanism and subsequent aging heat treatment. In order to further optimize the performance of maraging steel, it is particularly important to understand its microstructural changes. The distribution and characteristics of the original austenite grain boundaries directly affect the organizational morphology, distribution and interconnection of the martensite, which in turn affects the strength, toughness and fatigue resistance of the material after aging. By observing the original austenite grain boundaries, we can gain a deeper understanding of the phase transformation mechanism of the material during the heat treatment process.

[0003] The original austenite grain size has a great influence on the performance and phase transformation of maraging steel, so its display method has attracted much attention. Whether the original austenite grain boundary can be clearly displayed depends on many factors, such as the chemical composition, organization, heat treatment state, corrosion method, reagents and time of the sample. For example, when a 4% nitric acid alcohol solution is used to corrode steel materials, its austenite microstructure is displayed, and the grain boundaries are difficult to corrode. At present, there are many methods for corroding the original austenite grain boundaries, such as oxidation method, network ferrite method, network pearlite method, network cementite method, heating and slow cooling method, thermochemical etching method, etc. However, these methods or operations are very complicated and the results are not ideal. Therefore, it is urgent to develop a corrosion solution to display the original austenite grain boundaries of maraging steel. Summary of the invention

[0004] The purpose of the present invention is to provide an electrolytic etching solution and a method for displaying the original austenite grain boundaries of maraging steel. The present invention can accurately and clearly observe the original austenite grain boundaries through the configured electrolytic etching solution components, and then further determine the austenite grain size, which is of great significance for statistically analyzing the austenite grain size and realizing efficient and accurate acquisition of experimental data.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The invention provides an electrolytic corrosion solution, which comprises the following components: 5-6 ml of anhydrous ethanol, 2-3 ml of concentrated nitric acid, 1.5-2.5 ml of hydrochloric acid, 2-2.5 ml of deionized water, 1-2 g of copper sulfate and 1-2 g of copper chloride.

[0007] The present invention also provides a method for displaying the original austenite grain boundary of maraging steel, comprising the following steps:

[0008] (1) Austenitizing treatment: The maraging steel is heated in a protective atmosphere to obtain the austenite of the maraging steel;

[0009] (2) Electrolytic corrosion test: After the austenite of the maraging steel is ground and polished, it is placed in the electrolytic corrosion solution as described above for electrolysis until the austenite grain boundaries are clear, and the austenite grain size is counted.

[0010] Further, on the basis of the above technical solution, the maraging steel includes the following components by mass percentage: C: 0.10-0.14%; Si: 0.20-0.40%; Co: 1.0-15.0%; P: ≤0.020%; S: ≤0.010%; Cr: 4.50-10.50%; Mo: 1.00-10.60%; V: 0-1%; Ni: 5-12%; Nb: 0.1-0.5%; Al: 0.1-0.5%; Fe: balance.

[0011] Furthermore, based on the above technical solution, the austenite temperature of the maraging steel is 950-1350°C.

[0012] Further, on the basis of the above technical solution, the alloy composition of the maraging steel is obtained by high-throughput composition design using CALPHAD;

[0013] Preferably, the alloy raw material is a powder with a purity of ≥99.9wt%, and the particle size of the powder is 6-15 μm.

[0014] Further, on the basis of the above technical solution, in step (1), the heating temperature is 950-1350° C., preferably 980-1350° C.; the heating time is 20 min-2 h;

[0015] And / or, the protective atmosphere is one or more of argon, helium, and nitrogen;

[0016] And / or, in step (2), the grinding includes coarse grinding and fine grinding;

[0017] Among them, the rough grinding is to use 240# to 600# sandpaper for grinding;

[0018] Fine grinding is done by using 800# to 1200# sandpaper;

[0019] And / or, in step (2), the polishing is performed using a polishing agent;

[0020] The polishing agent refers to an aluminum oxide polishing agent with a particle size of 0.15 to 0.35 μm.

[0021] Further, based on the above technical solution, in step (2), the electrolysis conditions include:

[0022] And / or, the electrolysis voltage is 8-10V, and the electrolysis current is 2-5A / cm 2 , electrolyze 2 to 4 times, each electrolysis time is 8 to 12 seconds;

[0023] And / or, in step (2), counting the austenite grain size refers to using Nano Measurer 1.2 software to count the size of austenite grain boundaries.

[0024] Further, based on the above technical solution, the method for preparing the maraging steel comprises the following steps:

[0025] S1: Weigh the alloy powder raw material according to the designed composition, mix and solidify the alloy powder raw material and the degreasing agent, and then feed it into the injection molding machine for processing, and then perform degreasing treatment;

[0026] S2: The alloy billet after degreasing is subjected to isothermal and isobaric sintering to obtain maraging steel.

[0027] Further, on the basis of the above technical solution, in step S1, the mixing and solidification refers to mixing and stirring the alloy powder raw material and the degreasing agent in a mixing device;

[0028] and / or, the stirring speed is 20 to 50 r / min and the stirring time is 65 to 100 min;

[0029] And / or, in step S1, the heating temperature of the injection molding machine is 195-225°C; the heating time is 30-45 minutes;

[0030] And / or, in step S1, the heating temperature of the degreasing treatment is 125-135° C. and the heating time is 380-440 min;

[0031] and / or, the degreasing agent comprises oxalic acid or nitric acid;

[0032] And / or, in step S2, the temperature of the isothermal and isobaric sintering is 1200-1400° C. and the time is 24-36 hours.

[0033] The present invention also provides an application of the above-mentioned method for displaying austenite grain boundaries of maraging steel, which can be used to quantitatively detect the austenite grain size in a CoCrNiNbMoFe alloy system.

[0034] The present invention provides an electrolytic corrosion solution and a method for displaying the original austenite grain boundary of maraging steel, and the beneficial effects are as follows:

[0035] 1. The present invention uses a computational material design method to determine the alloy composition of maraging steel, and prepares maraging steel samples by metal injection molding. For the treated samples, by configuring the composition of the electrolytic etching solution, the grain boundaries of the original austenite can be accurately and clearly observed, and the grain size of the austenite can be further determined.

[0036] 2. The method for displaying the original austenite grain boundary of maraging steel provided by the present invention adopts an electrolytic etching solution formula that can replace the effect of picric acid, and can well display the original austenite grain boundary of maraging steel, and use NanoMeasurer 1.2 to count the size of the austenite grain boundary grain size. The etching solution formula in the present invention is simple, and can effectively display the original austenite grain boundary, and can fully reflect the grain size and uniformity of CoCrNiNbMoFe alloy steel after high-temperature austenitization, which is of great significance for counting the austenite grain size and realizing efficient and accurate acquisition of experimental data. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 A schematic diagram of the phase fraction of the Fe-8Co9Cr8Ni0.3Nb8Mo alloy according to Example 1 of the present invention changing with temperature;

[0039] Figure 2 Austenite grain boundary display diagram of Fe-8Co9Cr8Ni0.3Nb8Mo alloy kept at 1040°C for 30 minutes provided in Example 1 of the present invention;

[0040] Figure 3 Austenite grain boundary display diagram of Fe-8Co9Cr8Ni0.3Nb8Mo alloy kept at 980°C for 2h provided in Example 1 of the present invention;

[0041] Figure 4 This is a diagram showing the austenite grain boundaries of the Fe-10Co9Cr7Ni0.3Nb7.5Mo0.5V alloy kept at 1100°C for 2h provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0043] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0044] According to a first aspect of the present invention, an electrolytic etching solution is provided, which comprises the following components: 5-6 ml of anhydrous ethanol (for example, 5.2 ml, 5.4 ml, 5.6 ml, 5.8 ml, etc.), 2-3 ml of concentrated nitric acid (for example, 2.2 ml, 2.4 ml, 2.6 ml, 2.8 ml, etc.), 1.5-2.5 ml of hydrochloric acid (for example, 1.7 ml, 2.0 ml, 2.3 ml, etc.), 2-2.5 ml of deionized water, 1-2 g of copper sulfate (for example, 1.2 g, 1.4 g, 1.6 g, 1.8 g, etc.), and 1-2 g of copper chloride (for example, 1.2 g, 1.4 g, 1.6 g, 1.8 g, etc.).

[0045] Specifically, corrosion tests are generally carried out using a corrosion solution containing picric acid. However, as picric acid has been listed as a national controlled product, the use requirements are extremely strict, resulting in a gradual discontinuation of production. Therefore, there is an urgent need for a corrosion solution that does not contain picric acid and can be used to efficiently erode the austenite grain boundaries of maraging steel.

[0046] Specifically, copper sulfate and copper chloride are added to the etching solution provided by the present invention, the purpose of which is to cause the copper ions obtained by dissolving copper sulfate and copper chloride to undergo a substitution reaction with the iron ions on the alloy surface. Under the action of the substitution reaction, the copper ions will gradually replace the positions of some iron ions on the surface of the alloy, so that the austenite grain boundaries that were originally difficult to directly observe can be clearly displayed on the alloy surface. Austenite is an important phase structure in metal materials, and the clear identification of its grain boundaries is crucial for understanding the mechanical properties, corrosion resistance, and phase change behavior of the material during heat treatment.

[0047] As an optional embodiment of the present invention, the concentration ratio of the hydrochloric acid to the concentrated nitric acid is 1:1.

[0048] Specifically, the present invention limits the addition amount of hydrochloric acid and concentrated nitric acid because excessive addition of hydrochloric acid and concentrated nitric acid will accelerate the corrosion of the alloy surface, interfere with the replacement process of copper ions and iron ions, and affect the clear appearance of austenite grain boundaries.

[0049] According to a second aspect of the present invention, there is provided a method for displaying original austenite grain boundaries of maraging steel, comprising the following steps:

[0050] (1) Austenitizing treatment: The maraging steel is heated in a protective atmosphere to obtain the austenite of the maraging steel;

[0051] (2) Electrolytic corrosion test: After the austenite of the maraging steel is ground and polished, it is placed in the electrolytic corrosion solution as described above for electrolysis until the austenite grain boundaries are clear, and the austenite grain size is counted.

[0052] As an optional embodiment of the present invention, the maraging steel includes the following components by mass percentage: C: 0.10-0.14% (e.g., 0.11%, 0.12%, 0.13%, etc.); Si: 0.20-0.40% (e.g., 0.25%, 0.3%, 0.35%, etc.); Co: 1.0-15.0% (e.g., 4.0%, 6.0%, 8.0%, 10.0%, 12.0%, 14.0%, etc.); P: ≤0.020% (e.g., 0.010%, 0.005%, etc.); S: ≤0.010% (e.g., 0.005%, 0.001%, etc.); Cr: 4.50-10.50% (e.g., 0.11%, 0.12%, 0.13%, etc.); Such as 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, etc.); Mo: 1.00~10.60% (such as 4.0%, 6.0%, 8.0%, 10.0%, etc.); V: 0~1% (such as 0.40%, 0.60%, 0.80%, etc.); Ni: 5~12% (such as 6.0%, 8.0%, 10.0%, 11.0%, etc.); Nb: 0.1~0.5% (such as 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, etc.); Al: 0.1~0.5% (such as 0.2%, 0.3%, 0.4%, etc.); Fe: balance.

[0053] As an optional embodiment of the present invention, the austenite temperature of the maraging steel is 950-1350°C.

[0054] Specifically, the components of each element in the maraging steel provided in the present invention need to be within the above-mentioned limited range, otherwise the austenitizing temperature interval will be reduced. When the austenitizing interval is relatively large (950-1350°C), it means that there is more flexibility and choice space when performing heat treatment operations, and the expected microstructure and performance can be more easily achieved. In this interval, the material can better select the heat treatment process to obtain the required mechanical properties and stability. The higher the austenitizing temperature, the shorter the heat treatment time, and vice versa. The longer the heat treatment time will be. Among the many elements, the effect of Ni (nickel) on the austenite temperature interval is particularly significant. The Ni element plays an important role in steel. It can effectively expand the austenite zone, so that the material can still maintain the austenite state at a higher temperature. However, it is worth noting that although the Ni element has a positive effect on the expansion of the austenite interval, if the Ni content is too high, it will have an adverse effect on the plasticity and toughness of the material. Specifically, too high Ni content will lead to poor plasticity and toughness of the material, mainly because the increase of Ni element will change the lattice structure and phase transformation behavior of the material, thus affecting its mechanical properties and processing performance. In addition, the increase of Ni element will lead to increased costs. Therefore, when formulating maraging steel, the content of Ni element must be precisely controlled to ensure that the material has sufficient austenite range for heat treatment and maintains good plasticity and toughness to meet the needs of practical applications.

[0055] As an optional embodiment of the present invention, the alloy composition of the maraging steel is obtained by high-throughput composition design using CALPHAD.

[0056] As an optional embodiment of the present invention, the purity of the alloy raw material is ≥99.9wt% of powder, and the particle size of the powder is 6 to 15μm (such as 8μm, 10μm, 12μm, 14μm, etc.).

[0057] As an optional embodiment of the present invention, in step (1), the heating temperature is 950-1350°C (for example, 980°C, 1000°C, 1150°C, 1200°C, 1250°C, 1300°C, etc.), preferably 980-1350°C; the heating time is 20min-2h (for example, 40min, 60min, 80min, 100min, etc.).

[0058] Specifically, the present invention limits the heating temperature in step (1) to 950-1350°C, which is substantially the same as the austenite temperature range. This is because too high or too low a heating temperature will have adverse effects, so a relatively wide austenite temperature range is required to better perform heat treatment.

[0059] If the heating temperature of maraging steel is too low, the solid solution temperature may not be reached, so austenitization cannot be achieved. Austenite is a phase structure at a certain temperature, and the clear appearance of its grain boundaries is crucial to understanding the subsequent aging behavior and final performance of the material. However, when the heating temperature is low and the heat treatment time is short, austenite cannot be formed or is formed incompletely, which will make it difficult to see clear austenite grain boundaries in the subsequent microstructure observation, which in turn affects the accurate evaluation of the material properties. The length of the heating time is also determined by the heating temperature. During the heat treatment process, there is a balance between temperature and time. If the heating temperature is high, the required heat treatment time will be shortened accordingly, because high temperature can accelerate the diffusion of elements and phase transformation processes. However, if the heating time is too long, even at moderate temperatures, it may lead to adverse microstructural changes. In particular, excessively long heating time will lead to abnormal growth of austenite grains. This grain coarsening phenomenon will significantly reduce the mechanical properties of the material, such as strength, toughness and fatigue life. The growth of grains means a decrease in the number of grain boundaries, which weakens the positive effect of grain boundaries on material properties and increases defects and stress concentration points inside the material, thereby reducing the overall performance, affecting the corrosion of maraging steel in electrolytic corrosion solution, and ultimately affecting the display of the original austenite grain boundaries. Therefore, during the heat treatment of maraging steel, the heating temperature and heating time must be strictly controlled to ensure the ideal microstructure and excellent performance.

[0060] And / or, the protective atmosphere is one or more of argon, helium, and nitrogen.

[0061] Specifically, the maraging steel sample is placed in an argon-filled sealed tube at 900°C to 1350°C for 20min-2h for austenitization treatment, and then immediately placed in ice water for quenching to transform austenite into martensite. The purpose of austenitization treatment is to further improve the composition uniformity of austenite in maraging steel and refine austenite grains.

[0062] As an optional embodiment of the present invention, in step (2), the grinding includes coarse grinding and fine grinding;

[0063] Among them, the rough grinding is to use 240# to 600# sandpaper for grinding;

[0064] Fine grinding is done by using 800# to 1200# sandpaper;

[0065] And / or, in step (2), the polishing is performed using a polishing agent;

[0066] The polishing agent refers to an aluminum oxide polishing agent with a particle size of 0.15 to 0.35 μm.

[0067] Specifically, the maraging steel sample after austenitization is coarsely ground, and sandpaper with a grit of 240# to 600# is selected to remove surface irregularities and large defects. After coarse grinding, finer grit sandpaper (such as 800# to 1200#) is used for fine grinding to further flatten the sample surface and eliminate scratches left by coarse grinding. Polishing is performed using polishing paste and polishing cloth, and a grit of 0.25μm is usually selected to obtain a mirror effect. Maintain uniform and gentle pressure during polishing to avoid generating new scratches. The polished sample is placed in an ultrasonic cleaner and ultrasonically cleaned with an appropriate cleaning fluid (such as deionized water or alcohol) to remove residual polishing agent and impurities on the surface. Finally, the sample is blown dry with a hair dryer to ensure that there are no water marks and other contaminants on the surface, so that the test surface is bright and scratch-free.

[0068] As an optional embodiment of the present invention, in step (2), the electrolysis conditions include:

[0069] The electrolysis voltage is 8-10V, and the electrolysis current is 2-5A / cm 2 , electrolyze 2 to 4 times, each electrolysis time is 8 to 12 seconds.

[0070] As an optional implementation of the present invention, in step (2), counting the austenite grain size refers to using NanoMeasurer 1.2 software to count the size of austenite grain boundaries.

[0071] As an optional embodiment of the present invention, a method for preparing the above-mentioned maraging steel is provided, comprising the following steps:

[0072] S1: Weigh the alloy powder raw material according to the designed composition, mix and solidify the alloy powder raw material and the degreasing agent, and then feed it into the injection molding machine for processing, and then perform degreasing treatment;

[0073] S2: The alloy billet after degreasing is subjected to isothermal and isobaric sintering to obtain maraging steel.

[0074] Specifically, the present invention prepares metal powder according to the mass fraction according to the designed element composition, and prepares the steel ingot through the steps of powder solidification, powder injection, layer melting and post-processing. The process technology not only has the advantages of fewer conventional powder metallurgy processes, no cutting or less cutting, and high economic benefits, but also overcomes the shortcomings of traditional powder metallurgy products such as uneven material, low mechanical properties, difficulty in forming thin walls, and complex structures. It is particularly suitable for mass production of small, complex and special metal parts, and can produce high-alloy maraging steel.

[0075] As an optional embodiment of the present invention, in step S1, the mixing and curing refers to mixing and stirring the alloy powder raw material and the degreasing agent in a mixing device;

[0076] And / or, the stirring speed is 20-50 r / min (for example, 25 r / min, 30 r / min, 35 r / min, 40 r / min, 45 r / min, etc.), and the stirring time is 65-100 min (for example, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min, etc.).

[0077] As an optional embodiment of the present invention, in step S1, the heating temperature of the injection molding machine is 195-225°C (for example, 200°C, 205°C, 210°C, 215°C, 220°C, etc.); the heating time is 30-45min (for example, 33min, 35min, 37min, 40min, 43min, etc.).

[0078] As an optional embodiment of the present invention, in step S1, the heating temperature of the degreasing treatment is 125-135° C. (for example, 127° C., 129° C., 130° C., 132° C., 134° C., etc.); the heating time is 380-440 min (for example, 390 min, 400 min, 410 min, 420 min, 430 min, etc.);

[0079] And / or, the degreasing agent includes oxalic acid or nitric acid.

[0080] As an optional embodiment of the present invention, in step S2, the temperature of the isothermal and isobaric sintering is 1200-1400°C (such as 1250°C, 1300°C, 1350°C, etc.), and the time is 24-36h (such as 28h, 30h, 32h, 34h, etc.).

[0081] According to a third aspect of the present invention, there is provided an application of the above-mentioned method for displaying austenite grain boundaries of maraging steel, which can be used for quantitatively detecting austenite grain size in a CoCrNiNbMoFe alloy system.

[0082] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0083] Example 1

[0084] A method for displaying austenite grain boundaries of maraging steel in a CoCrNiNbMoFe alloy system comprises the following steps:

[0085] 1. Alloy design and sample preparation: The CoCrNiNbMoFe alloy composition was designed by high-throughput composition using the CALPHAD method, and the phase fraction of the CoCrNiNbMoFe alloy was obtained. Figure 1As shown, it is Fe-8Co9Cr8Ni0.3Nb8Mo, and the austenitizing temperature range is 938-1345°C. As the temperature decreases, some phases such as bcc, C14, and L12 will gradually precipitate. Based on the calculation results, the alloy composition of the maraging steel is 8wt.% Co, 9wt.% Cr, 8wt.% Ni, 0.3wt.% Nb, 8wt.% Mo, and Fe as a balance. The raw material of the alloy composition is a metal powder product with a purity of ≥99.9wt% and a particle size of 10μm.

[0086] First, configure the powders of each element according to the alloy composition designed above, mix and solidify the configured alloy powder and oxalic acid in a mixing device, preferably, the output shaft speed can be smoothly adjusted from 30r / min, and processed by a plunger injection machine, wherein the heating temperature during the injection process is: 200℃, the heating time is: 40min, the heating temperature of the degreasing treatment is 130℃; the heating time is 400min, and finally it is treated in a high-temperature sintering furnace for 36h, wherein the heat treatment temperature of the high-temperature sintering furnace is 1200℃, so that it is isothermal and isobaric sintering. The austenitizing treatment temperatures of the maraging steel alloy samples are 980℃ and 1040℃, respectively, and the time is 2h and 30min, respectively. The purpose of the austenitizing treatment is to further improve the composition uniformity of the austenite of the maraging steel and to refine the austenite grains.

[0087] 2. Electrolytic corrosion test: Use 500# sandpaper for coarse grinding and 1000# sandpaper for fine grinding. Polish with 0.25μm alumina polishing agent and place in electrolytic corrosion solution for electrolysis.

[0088] The composition and proportion of the electrolytic corrosion solution are: 5 ml of anhydrous ethanol, 2 ml of concentrated nitric acid, 1.5 ml of hydrochloric acid, 2.5 ml of deionized water, 2 g of copper sulfate, and 2 g of copper chloride. During the electrolysis process, the electrolysis voltage is 9 V and the electrolysis current is 3 A / cm 2 , electrolyze 4 times, each time for 10 seconds, and observe the microstructure morphology after each electrolysis until the austenite grain boundary is clear. The austenite grain boundary of Fe-8Co9Cr8Ni0.3Nb8Mo alloy kept at 1040℃ for 30min is shown in the figure below Figure 2 As shown; the austenite grain boundary of Fe-8Co9Cr8Ni0.3Nb8Mo alloy kept at 980℃ for 2h is shown in the figure Figure 3 As shown;

[0089] 3. Statistics of austenite grain size: Nano Measurer 1.2 software is used to count the size of austenite grain boundaries. Figure 2 and Figure 3 As shown, the statistical results are 16.69μm and 10.09μm respectively.

[0090] Example 2

[0091] A method for displaying austenite grain boundaries of maraging steel in a CoCrNiNbMoFe alloy system comprises the following steps:

[0092] 1. Alloy design and sample preparation: The CoCrNiNbMoFe alloy composition was designed by high-throughput composition using the CALPHAD method, and the phase fraction of the CoCrNiNbMoFeV alloy was obtained. Figure 1 As shown, it is Fe-10Co9Cr7Ni0.3Nb7.5Mo0.5V, the austenitizing temperature range is 950 to 1360°C, and based on the calculation results, the maraging steel alloy composition is 10wt.% Co, 9wt.% Cr, 7wt.% Ni, 0.3wt.% Nb, 7.5wt.% Mo, 0.5wt.% V, Fe balance, and the alloy component raw material is a metal powder product with a purity of ≥99.9wt% and a particle size of 10μm.

[0093] First, configure the powders of each element according to the alloy composition designed above, mix and solidify the configured alloy powder and nitric acid in a mixing equipment, preferably, the output shaft speed can be smoothly adjusted from 30r / min, and processed by a plunger injection machine, wherein the heating temperature during the injection process is: 225°C, the heating time is: 30min, the heating temperature of the degreasing treatment is 135°C; the heating time is 380min, and finally it is treated in a high-temperature sintering furnace for 36h, wherein the heat treatment temperature of the high-temperature sintering furnace is 1200°C, so that it is isothermal and isobaric sintering. The austenitizing treatment temperature of the maraging steel alloy sample is 1100°C, and the time is 2h. The purpose of the austenitizing treatment is to further improve the composition uniformity of the austenite of the maraging steel and to refine the austenite grains.

[0094] 2. Electrolytic corrosion test: 400# sandpaper is used for coarse grinding, 1200# sandpaper is used for fine grinding, 0.15μm alumina polishing agent is used for polishing, and electrolysis is carried out in electrolytic corrosion solution;

[0095] The composition and proportion of the electrolytic corrosion solution are: 5 ml of anhydrous ethanol, 2 ml of concentrated nitric acid, 1.5 ml of hydrochloric acid, 2.5 ml of deionized water, 2 g of copper sulfate, and 2 g of copper chloride. During the electrolysis process, the electrolysis voltage is 10 V and the electrolysis current is 4 A / cm 2 , electrolyze 3 times, each time for 10 seconds, and observe the microstructure morphology after each electrolysis until the austenite grain boundary is clear. The austenite grain boundary of Fe-10Co9Cr7Ni0.3Nb7.5Mo0.5V alloy kept at 1000℃ for 2h is shown in the figure Figure 4 As shown:

[0096] 3. Statistics of austenite grain size: Nano Measurer 1.2 software is used to count the size of austenite grain boundaries. Figure 4 As shown, the statistical result is 95.1μm.

[0097] Comparative Example 1

[0098] Patent CN201210015915 discloses a method for displaying the original austenite grain boundaries of P91 and P92 steels, which requires two-step corrosion. The first step uses chemical hot corrosion of 1-6g sodium dodecylbenzene sulfonate or sodium tridecylbenzene sulfinate, 80-120ml supersaturated picric acid aqueous solution, and 1-6ml hydrogen peroxide. The polished sample is immersed in the chemical corrosion solution, heated and boiled for etching for 2-5 minutes, and then the sample is taken out for cleaning and drying; the second step is an electrolytic etching solution with a 5-20% sulfuric acid aqueous solution; electrolysis specifications: voltage 15-25V, time 50-90s;

[0099] This etching method requires two etchings, and the etching solution contains picric acid. As the production of picric acid is discontinued, the etching solution cannot be successfully prepared. In addition, the combination of one boiling etching and electrolytic corrosion will make the operation more complicated and difficult to master.

[0100] Comparative Example 2

[0101] Patent application document CN110132962A discloses a method for etching the grain boundaries of the original austenite grains of tempered bainite steel for boilers and pressure vessels, wherein the etching solution includes 8-15g sulfosalicylic acid, 100mL water, 1-3g sodium dodecylbenzene sulfonate and 0.5-3mL concentrated nitric acid. During electrolysis, the first voltage is 0.2-1V, the time is 10-15s, and the second voltage is 5-8V, the time is 5-10s.

[0102] However, since this method requires at least two or more times of corrosion with different electrolytic parameters, it is difficult for the operator to master the corrosion skills.

[0103] The differences between Example 1 and Comparative Example 1 and Comparative Example 2 are shown in Table 1:

[0104]

[0105] By comparing Example 1 of the present invention with Comparative Example 1, it can be seen that the different compositions, austenitizing temperatures and times of the prepared maraging steels will affect the austenitizing temperature and grain size, and further affect the clarity of the corroded grain boundaries.

[0106] The etching solutions of Examples 1 and 2 are first subjected to thermal etching and then electrolysis, while Example 2 requires multiple etchings at different currents and voltages, which are both difficult for operators to master the operating skills. The present invention only needs to be electrolyzed at the same voltage, which is convenient for researchers to operate and saves researchers time.

[0107] Comparative Example 3

[0108] The difference between this comparative example and Example 1 is that the electrolytic etching solution does not contain copper sulfate and copper chloride. The composition and proportion of the etching solution in this comparative example are: 5 ml of anhydrous ethanol, 2 ml of concentrated nitric acid, 1.5 ml of hydrochloric acid, and 2.5 ml of deionized water. The remaining technical parameters and operating steps are the same as those in Example 1.

[0109] After multiple (≥4) electrolysis, the comparative example still cannot observe clear austenite grain boundaries. This is because the etching solution does not contain copper sulfate and copper chloride, and copper ions cannot be decomposed to undergo substitution reaction with iron ions in the alloy, resulting in the inability to observe clear austenite grain boundaries.

[0110] Comparative Example 4

[0111] The difference between this comparative example and Example 1 is that an excess of hydrochloric acid is added to the electrolytic etching solution. The components and proportions of the etching solution in this comparative example are: 5 ml of anhydrous ethanol, 1 ml of concentrated nitric acid, 10 ml of hydrochloric acid, 2.5 ml of deionized water, 2 g of copper sulfate, and 2 g of copper chloride. The remaining technical parameters and operating steps are the same as those in Example 1.

[0112] After multiple (≥4) electrolysis, the austenite grain boundaries in this comparative example are still not clearly observed. This is because too much hydrochloric acid is added to the etching solution, which causes the corrosion rate of the alloy surface to be too fast, interfering with the normal replacement process of copper ions and iron ions in the etching solution, and ultimately affecting the clear appearance of the austenite grain boundaries.

[0113] Comparative Example 5

[0114] The difference between this comparative example and Example 1 is that the austenitizing temperature of the maraging steel alloy sample Fe-8Co9Cr8Ni0.3Nb8Mo is 950°C and the heating time is 5 hours. The other technical parameters and operation steps are the same as those of Example 1.

[0115] After four electrolysis cycles, the austenite grain boundary clarity observed in this comparative example is poor. This is because the austenitizing treatment temperature of the maraging steel alloy is low, resulting in a longer heating time, which leads to abnormal growth of austenite grains and affects the austenite grain boundary clarity.

[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrolytic corrosion solution, characterized in that: The invention comprises the following components: 5-6 ml of anhydrous ethanol, 2-3 ml of concentrated nitric acid, 1.5-2.5 ml of hydrochloric acid, 2-2.5 ml of deionized water, 1-2 g of copper sulfate and 1-2 g of copper chloride.

2. A method for displaying the original austenite grain boundary of maraging steel, characterized in that: The steps include: (1) Austenitizing treatment: The maraging steel is heated in a protective atmosphere to obtain the austenite of the maraging steel; (2) Electrolytic corrosion test: After the austenite of the maraging steel is polished, it is placed in the electrolytic corrosion solution as described in claim 1 for electrolysis until the austenite grain boundaries are clear, and the austenite grain size is counted.

3. The method for displaying the original austenite grain boundary of maraging steel according to claim 2 is characterized in that: The maraging steel comprises the following components by mass percentage: C: 0.10-0.14%; Si: 0.20-0.40%; Co: 1.0-15.0%; P: ≤0.020%; S: ≤0.010%; Cr: 4.50~10.50%; Mo: 1.00~10.60%; V: 0~1%; Ni: 5~12%; Nb: 0.1~0.5%; Al: 0.1~0.5%; Fe: balance.

4. The method for displaying the original austenite grain boundary of maraging steel according to claim 2, characterized in that: The austenite temperature of the maraging steel is 950-1350°C.

5. The method for displaying the prior austenite grain boundary of maraging steel according to claim 2, characterized in that: The alloy composition of the maraging steel is obtained by high-throughput composition design using CALPHAD; Preferably, the alloy raw material is a powder with a purity of ≥99.9wt%, and the particle size of the powder is 6-15 μm.

6. The method for displaying the prior austenite grain boundary of maraging steel according to claim 2, characterized in that: In step (1), the heating temperature is 950-1350° C., preferably 980-1350° C.; the heating time is 20 min-2 h; And / or, the protective atmosphere is one or more of argon, helium, and nitrogen; And / or, in step (2), the grinding includes coarse grinding and fine grinding; Among them, the rough grinding is to use 240# to 600# sandpaper for grinding; Fine grinding is done by using 800# to 1200# sandpaper; And / or, in step (2), the polishing is performed using a polishing agent; The polishing agent refers to an aluminum oxide polishing agent with a particle size of 0.15 to 0.35 μm.

7. The method for displaying the prior austenite grain boundary of maraging steel according to claim 2, characterized in that: In step (2), the conditions for electrolysis include: And / or, the electrolysis voltage is 8-10V, and the electrolysis current is 2-5A / cm 2 , electrolyze 2 to 4 times, each electrolysis time is 8 to 12 seconds; And / or, in step (2), counting the austenite grain size refers to using Nano Measurer 1.2 software to count the size of austenite grain boundaries.

8. The method for displaying the prior austenite grain boundary of maraging steel according to claim 2, characterized in that: The method for preparing the maraging steel comprises the following steps: S1: Weigh the alloy powder raw material according to the designed composition, mix and solidify the alloy powder raw material and the degreasing agent, feed it into the injection molding machine for processing, and then perform degreasing treatment; S2: The alloy billet after degreasing is subjected to isothermal and isobaric sintering to obtain maraging steel.

9. The method for displaying the prior austenite grain boundary of maraging steel according to claim 8, characterized in that: In step S1, the mixing and curing refers to mixing and stirring the alloy powder raw material and the degreasing agent in a mixing device; and / or, the stirring speed is 20 to 50 r / min and the stirring time is 65 to 100 min; And / or, in step S1, the heating temperature of the injection molding machine is 195-225°C; the heating time is 30-45 minutes; And / or, in step S1, the heating temperature of the degreasing treatment is 125-135° C. and the heating time is 380-440 min; and / or, the degreasing agent comprises oxalic acid or nitric acid; And / or, in step S2, the temperature of the isothermal and isobaric sintering is 1200-1400° C. and the time is 24-36 hours.

10. An application of the method for displaying austenite grain boundaries of maraging steel according to any one of claims 2 to 9, characterized in that: It can be used to quantitatively detect the austenite grain size in the CoCrNiNbMoFe alloy system.

Citation Information

Patent Citations

  • Method for displaying P91 and P92 steel original austenite grain boundaries

    CN102590050A

  • Method for displaying prior austenite grain boundary of tempered bainite steel for boiler and pressure vessel

    CN110132962A